Closure of the appendiceal stump in laparoscopic appendectomy: A systematic review of the literature. (September 2020) - Makaram, N.; Knight, S.R.; Ibrahim, A.; Patil, P.; Wilson, M.S.J.
Abstract: Background: Closure of the appendiceal stump is a key step performed during laparoscopic appendicectomy. Inadequate management of the appendiceal stump has the potential to cause significant morbidity. Several methods of stump closure have been described, however high-level evidence is limited. We performed a systematic review evaluating clinical outcomes and quality of the evidence for the methods of appendiceal stump closure. Methods: A systematic literature search was performed using Medline, Embase, Cochrane Database and Google Scholar to identify studies comparing appendiceal stump closure methods in laparoscopic appendectomy for acute appendicitis from inception to October 2019. Data regarding operative duration, peri-operative complications, length of stay and costs were collated from all included studies. Results: From 160 identified studies, 19 met the inclusion criteria. Endoloops and endoclips provide equivalent clinical outcomes at lower cost, while operative duration was shortest with endoclip closure. Endostapler devices have the lowest rate of peri-operative complications (3.56%), however their cost limits their regular use in many healthcare environments. Post-operative complication rate and length of stay were similar for all stump closure methods. Conclusion: Although there are no significant differences in method of stump closure in laparoscopic appendectomy, closure with endoclips provides the shortest operative duration. There is a need for robust and standardized reporting of cost data when comparing stump closure methods, together with higher level evidence in the form of multi-centre randomized controlled trials before firm conclusions can be drawn regarding the optimal method of stump closure. Highlights: Currently there is no robust higher order evidence which assesses clinical outcomes, cost and time efficiency of methods of stump closure in laparoscopic appendicectomy. This is the first systematic review to investigate clinical outcomes, cost and quality of current evidence for all methods of laparoscopic appendiceal stump closure in acute appendicitis. No difference was observed in methods of stump closure in complication rate, length of stay, cost, and time efficiency. Endostaplers appear to provide most robust closure, albeit at a higher economic cost. Endoloops appear to provide efficient and successful closure, and are currently the most frequently studied method of closure.